Confirming the factor structure of the Francis Psychological type Scales (FPTS) among a sample of Anglican clergy in Wales - Payne, V. John (Mental health, religion & culture, 2021)
The Francis Psychological Type Scales were designed to provide a fresh conceptualisation and operationalisation of the four constructs underpinning psychological type theory (introversion – extraversion, sensing – intuition, thinking – feeling, judging – perceiving) in a way accessible for self-report surveys within church congregations and among religious leaders. The present study tests the factor structure of this instrument among 364 Anglican clergy serving in the Church in Wales. The varimax rotated solution with Kaiser normalisation recovered the hypothesised location of 39 of the 40 pairs of items across four factors with factor weightings above .38. The Francis Psychological Type Scales are commended for use.